DESAIN PRAKTIS MANAJEMEN MATERIAL PADA DEPARTEMEN PRODUKSI DENGAN PRINSIP NERACA MASSA - S. Murdapa, Petrus (Widya Warta, 2015)
This study discusses the conceptual errors that occur in the management of production material. The errors concern the quantity which had to be precisely measured, but was set for its value and vice versa. Consequently, the  accountability was neglected. The method of analysis was principally the correct application of mass balance in the management and control of the production material together with a proper degree of freedom evaluation.  A case and hypothetical data were used for the delineation of their application. The case was adopted  from a production department which was temporarily uninterrupted in nature. The analysis was done with the following stages. Firstly, it disclosed a scheme of simple management proposal. Secondly, it displayed a discussion on degrees of freedom in the use of the mass balance equation. The results indicated that the errors were not the quantity of observations; hence,  they were not independent. The value should be calculated on the quantities of other observations. Then, the accountability of production material management could be saved.